Online medical consultation: covid-19 system using software object-oriented approach - Ali Yahya Gheni; Hiba Adil Yousif; Yusmadi Yah Jusoh (Institute of Advanced Engineering and Science, 2021)
The internet has been a source of medical information, it has been used for online medical consultation (OMC). OMC is now offered by many providers internationally with diverse models and features. In OMC, consultations and treatments are available 24/7. The covid-19 pandemic across-the-board, many people unable to go to hospital or clinic because the spread of the virus. This paper tried to answer two research questions. The first one on how the OMC can help the patients during covid-19 pandemic. A literature review was conducted to answer the first research question. The second one on how to develop system in OMC related to covid-19 pandemic. The system was developed by Visual Studio 2019 using software object-oriented approach. Online expert review was conducted within 6 experts from health and academic industry to verify the model. Also, the system was validated by 11 users from heath and academic industry to confirm its usability. The statistical package for social science (SPSS 22) was used to analyze the collected data. The result of expert review confirmed that covid-19 system can help the patients. Also, the validity of the system was confirmed by 11 users from health and academic industry.